The inspection panel : (The World Bank, 2006)
The Annual Report of the Inspection Panel for the period July 1, 2005, to June 30, 2006 has been prepared for the International Bank for Reconstruction and Development and the International Development Association in accordance with the 1993 Resolution establishing the Panel. It is being circulated to the President and to the Executive Direc-tors of these institutions.